Lymphatic endothelium in health and disease - Jurisic, Giorgia; Detmar, Michael (Cell and tissue research, 2009)
The lymphatic vascular system has an important role in the maintenance of tissue fluid pressure homeostasis, in the mediation of the afferent immune response via recruitment of antigen-presenting cells toward draining lymph nodes, and in the intestinal absorption of dietary lipids. Substantial progress in our understanding of the development and the molecular mechanisms controlling the lymphatic system has been made during the last few years, based on a recent wave of discoveries of lymphatic endothelial cell-specific markers and growth factors. This has also led to new insights into the role of lymphatic endothelium in a number of diseases, including primary and secondary lymphedemas. The emerging role of lymphatic endothelium in the context of inflammation indicates that therapeutics targeting the lymphatic vasculature might represent a new strategy for anti-inflammatory therapies.